JURIDICAL REVIEW OF HEALTH PERSONEL PROTECTION AS A LEADING GUARD IN EFFORTS TO ACCELERATE THE HANDLING OF COVID-19: A NARRATIVE REVIEW - Vera Rimbawani Sushanty (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2021)
Health workers who are handling patient of SARS-CoV-2 (Severe Acute Respiratory Syndrome Corona Virus 2) or better known as the Coronavirus are legal subjects who carry out their obligations properly at their leader command, ruled accordance with the legal corridors, obtained the law right and protected from positive legal norms. This narrative research aims juridical review for protection the health workers during coronavirus pandemic. Using literature that obtained by looking materials and sources that match the theme and related them. Protection of health workers as the frontline in efforts to accelerate the handling of the coronavirus pandemic. Civil Servants who served during the Covid-19 pandemic will get a promotion one level higher. The incentive budget for medical personnel comes from a budget reallocation that has been set by Mr. President Joko Widodo for 16.63 trillion in 2020. This award is in the form of compensation and for health workers who fail, the government awards “Bintang Jasa Pratama” and “Bintang Jasa Nararya”. The government provides protection by issuing various policies to protect health workers as the frontline in efforts to accelerate the handling of coronavirus disease 2019. Keywords: Health workers, legal protection, Covid-19.